Reliability of Self-Reported Gleason Scores in Studies of Sexual Minority Prostate Cancer Survivors. Issue 3 (21st May 2020) - Rosser, B. R. Simon; Konety, Badrinath R.; Capistrant, Benjamin D.; Kapoor, Aditya; Polter, Elizabeth
Abstract: Introduction: In 2 studies prostate cancer survivors who were gay, bisexual or other men who had sex with men reported lower Gleason scores than heterosexual prostate cancer survivors. These results led some to speculate that men who have sex with men may undergo more intensive screening. Methods: In the largest study to date of prostate cancer survivors who were gay, bisexual or other men who have sex with men 23 of 193 participants (11.9%) reported low Gleason scores (2 to 5). We attempted to contact these individuals and received replies from 14, for a 61% participation rate. Results: At the second inquiry most men clarified that they reported only a partial Gleason score rather than the sum score. They clarified that they interpreted the question to refer to their most common cell morphology score (scored 1 to 5) rather than their total Gleason sum. Conclusions: We found that the average lower score in this population was not a result of differences in screening, but likely a measurement error. We propose a revised Gleason item question to overcome this research artifact.